The Influence of Cultural Factors on International Business PT Mayora Indah Tbk - Devina Wistiasari; Nathania Jocelyn; Sherlyca Styvani; Vonnylia Vonnylia; Windy Wihue Tarekar; Florensia Sutjiali (Universitas Muhammadiyah Makassar, 2024)
This article contains an analysis of the influence of cultural factors on international business at PT Mayora Indah Tbk which consists of managerial orientations, the four risks of international business, and SWOT analysis at PT Mayora Indah Tbk. The qualitative method is a method used by researchers to analyze companies by means of secondary data analysis. The results of the study show that PT Mayora Indah Tbk is able to meet the market in Indonesia so that it is able to develop to a larger stage with target markets namely countries in Asia, and the company still has to increase product innovation, promote its products in international markets, and make strategies appropriate marketing in order to develop its international business.